Multiple metastases from myxoid liposarcoma (MLS) for which Whole Body MRI (WB-MRI) was useful for their detection. Issue 9 (2018) - Nakanishi, Katsuyuki; Imura, Yoshinori; Nagata, Shigenori; Tsukabe, Akio; Naka, Norifumi; Nakatsuka, Shinichi; Tomiyama, Noriyuki
No abstract available